ANALISIS PEMBOROSAN PADA PROSES PRODUKSI COIL WIRE ROD SECTION 5,5 DENGAN PENDEKATAN LEAN MANUFACTURING DAN SIMULASI DI PT TMS - Aini Naqisy Muslich (2021)
PT TMS is one of the manufacturing companies, especially steel production with one of the products produced is Wire Rod. Low wire steel or wire rod is a type of rolled steel produced from billets that have a round cross section. In this study includes the production process of coil wire rod section 5.5 which belongs to the category of products that are the highest demand. This product has high demand, but several products have not complied with the standards that have been determined because of waste in the production process. The purpose of this research is to provide proposed improvements to reduce waste that occurs during the production process as well as provide a better production system design based on the results of implementation through simulations using ProModel Software. The method used starts from Questionnaire 7 Waste, Value Stream Analysis Tools, Big Picture Mapping, Fishbone Chart, Failure Mode Effect Analysis and then continued with simulation using ProModel Software. The results showed that provided proposed improvements can reduce lead time from 23268.183 seconds or 387.80 minutes to 21084.791 seconds or 351.41 minutes. In addition, it can increase productivity with an increase in production output up to 15%.